Non-Cancer Pain in the Adult Population: An Integrative Review - Mohammed, Alqahtani Jawhrah (International Journal of Innovative Research in Medical Science, 2019)
Pain is a global phenomenon with significant physical, psychological, financial, and social impacts. The number of patients with pain has increased globally, due to the increase in the complexity of the pain and its classifications. Despite pain’s high prevalence and economic impact, this phenomenon is not well investigated and understood. Understanding the concept of adult, non-cancer pain via the Specificity Theory and the Gate Control Theory of Pain is critical for professionals to expand the understanding of pain and ensure the best care. The purpose of this integrative review paper was to conduct a concept identification and analysis on pain through analyzing the existing literature. As the literature was reviewed, three major concepts emerged. Suffering, discomfort, and coping were the most frequent concepts that emerged, which is consistent with several studies of different populations, utilizing quantitative and qualitative methods. As pain concept is relevant to patient care and nursing practice, pain needs to be investigated by healthcare professionals and nursing research to provide a complete picture of the nature and pattern of pain in patients with chronic conditions such as genetic disorders, and in generating more knowledge about patient experiences. The importance of understanding and viewing pain via multiple lenses allows all to understand pain as multifaceted, complex, and interdisciplinary issues for which several of the causes are the social determinants of health.